Thermally treated Mytilus coruscus shells for fluoride removal and their adsorption mechanism - Lee, Jae In; Kang, Jin Kyu; Hong, Seung Hee; Lee, Chang Gu; Jeong, Sanghyun; Park, Seong Jik (Chemosphere, 2021)
We evaluated Mytilus coruscus shells (MCS) as an adsorbent for fluoride removal. Its removal efficiency was enhanced by thermal treatment and MCS at 800 °C (MCS-800) increased significantly its fluoride adsorption capacity from 0 to 12.28 mg/g. While raw MCS is mainly composed of calcium carbonate (CaCO3), MCS-800 consisted of 56.9% of CaCO3 and 43.1% of calcium hydroxide (Ca(OH)2). The superior adsorption capacity of MCS-800 compared to untreated MCS can be also explained by its larger specific surface area and less negative charge after the thermal treatment. X-ray photoelectron spectroscopy and X-ray diffraction analysis revealed that the fluoride adsorption of MCS-800 occurred via the formation of calcium fluorite (CaF2). Fluoride adsorption of MCS-800 approached equilibrium within 6 h and this kinetic adsorption was well-described by a pseudo-second-order model. The Langmuir model was suitable for describing the fluoride adsorption of MCS-800 under different initial concentrations. The maximum fluoride adsorption amount of MCS-800 was 82.93 mg/g, which was superior to those of other adsorbents derived from industrial byproducts. The enthalpy change of fluoride adsorption was 78.75 kJ/mol and the negative sign of free energy indicated that this phenomenon was spontaneous. The increase of pH from 3.0 to 11.0 slightly decreased the fluoride adsorption capacity of MCS-800. The adsorption was inhibited in the presence of anions and their impact increased with following trend: chloride < sulfate < carbonate < phosphate. The fluoride adsorption capacities of MCS-800 after washing with deionized water and 0.1 M NaOH were reduced by 31.5% and 57.4%, respectively.
Keywords: Adsorption capacities; Adsorption mechanism; Calcium hydroxide (Ca2); Fluoride adsorptions; Industrial by-products; Initial concentration; Pseudo-second order model; Removal efficiencies; Adsorption; Animals; Fluorides; Hydrogen-Ion Concentration; Kinetics; Mytilus; Water Pollutants, Chemical; Water Purification; Adsorption mechanism; Fluoride removal; Mussel shell; Mytilus coruscus; Thermal treatment